2012
DOI: 10.3144/expresspolymlett.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

New crosslinked hydrogels derivatives of 2-hydroxyethyl methacrylate: Synthesis, modifications and properties

Abstract: Abstract. This paper presents the synthesis, physicochemical properties and modifications of 2-hydroxyethyl methacrylate copolymers. It describes the new 2-hydroxyethyl methacrylate hydrogels in the form of microbeads of different degrees of crosslinking (2, 5, 8, 10, 15 and 20% mol). As crosslinking monomers bis[4(2-hydroxy-3-methacryloyloxypropoxy) phenyl]-sulfide and ethylene glycol dimethacrylate were used. The new hydrogels were obtained by two alternative methods in a suspension copolymerisation procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Such materials are widely used in agriculture, biomedicine, tissue engineering and as sorbents in the textile industry for removal of dyes and heavy metal ions. They generally contain -OH, -NH 2 , -COOH, -CONH 2 and -SO 3 functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Such materials are widely used in agriculture, biomedicine, tissue engineering and as sorbents in the textile industry for removal of dyes and heavy metal ions. They generally contain -OH, -NH 2 , -COOH, -CONH 2 and -SO 3 functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account, the utilization of polymeric microspheres in the field of chromatography, control of the particle size, the size distribution, the polymer composition, porosity, and functionality should be especially considered. Functionality can be introduced onto the particle surface by applying functional monomers [1][2][3][4] that can also play the role of crosslinking agents [5,6]. A more complicated route of functionalizing the surface of microspheres is the incorporation into the polymer network of a reactive monomer capable of derivatization, e.g., epoxide rings or chloroalkyl moiety [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption bands at 1705 and 1690 cm Figure 2 shows the thermal degradation of PMAA and P(MAA-MA5) samples by weight loss as a function of temperature. It was observed that there was no weight loss up to 75 °C and 150 °C for both PMAA and P(MAA-MA5), respectively which can be related to water molecules loss 20,21 . PMAA and P(MAA-MA5) hydrogels present sharp weight loss at 260 °C and 395 °C respectively, indicating the decomposition of the hydrogels backbone.…”
Section: Ftir Spectramentioning
confidence: 98%